Ef!luent Changing Interval Effects on hydration properties and milling recovery oftwodifferent RiceVarieties. - Vijitha, V.; Thushyanthy, A.; Prabhaharan, M. (University of Jaffna, 2020)
Parboiling is the hydrothermal treatment applied to the paddy grains before milling in order to increase the milling recovery. Parboiling process consist three stages such as soaking, steaming and drying. In this study the effects of effluent changing interval on milling yield of two different paddy varieties were estimated. In addition to that, the evaluation of characteristic effluent and hydro profile of paddy also were done. Paddy varieties of Department recommended variety BG 360 and industrial preference variety Addakari were soaked in water at ambient temperature. Two experimental setups were designed for both varieties with changing the effluent at each 12 hour interval and 24 hour interval within 48 hour duration. At every 6 hour interval, effluent samples were collected for characterization. After 48 hours of soaking, paddy grains were steamed till few of their hulls split off. It was then cooled and sun dried until the moisture reduced up to 14%. Analytical grade de-husking and polishing machines were used for the milling. In the milling yield analysis, Addakari rice variety with changing the effluent at 12 hour interval resulted higher, total milled rice yield percentage, brown rice percentage and degree of milling percentage as 73.66%, 81.77% and 90.08%, respectively. The head rice percentage was 68.26 % to the same variety butwith changing the effluent at 24 hour interval.The rice varietyBG 360 with effluent changed at 24hr interval yielded higher hull percentage as 21.66%. The whiteness value of BG 360 with changing the effluent at 12 hour interval was higher than other treatment and that of other variety as 27.8%. It resulted in higher hydration profile of BG 360 rice variety, due to the larger surface area. When considering the effluent characteristic with different changing interval of effluent, the treatment with time interval of 12 hour showed lesser level contaminants in the effluent, which can be utilized for the secondary purposes like irrigation. According to this study, it was identified that effluent changing interval, influences the milling yield, hydration profile and physical properties of different rice varieties.
Keywords: Drying.; Effluent.; Head rice percentage.; Milling yield.; Parboiling.; Soaking